PENGARUH STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS - Dede Suharna; Silviyanti Silviyanti (Universitas La Tansa Mashiro, 2019)
Hundreds of companies have now implemented comprehensive strategic planning in their efforts to achieve higher profit earnings (profit oriented). Long-term goals show the expected results by carrying out certain strategies that have been set. In general, a company is founded with the aim of obtaining maximum profitability, because profit is a supporting factor for a company's survival The population of this study is the basic industrial sector and chemical manufacturing companies listed on the Indonesia Stock Exchange 2016-2018 research period. The method of determining the sample using purposive sampling, with several criteria determined then taken 33 samples with secondary research data obtained from the Indonesia Stock Exchange (IDX) in 2016 up to 2018. To answer the research problem and test the research hypothesis the path analysis technique was used (Analysis Multiple Linear Regression) and its tools use the SPSS version 20 application The results showed that: 1. capital structure has a positive effectand significant to profitability with a value of Tcount 2,938 ≥ Ttable 2,039, 2. company growth has no significant effect on profitability, with a value of Tcount -0,011 ≤ Ttable 2,039 3. capital structure and company growth have a positive and significant effect on profitability with a value of Fcount 4.779 ≥ Ftable 4 , 51. It can be concluded that through the F test capital structure and company growth have a significant effect on the profitability of manufacturing companies in the basic industrial and chemical sectors in the period 2106-2018. financial data because of inappropriate data will hamper the smooth running of the research, and is expected to expand the sample of companies listed on the Indonesia Stock Exchange